Fetal human leukocyte antigen-C and maternal killer-cell immunoglobulin-like receptors in cases of severe preeclampsia. (January 2019) - Larsen, Tine Graakjær; Hackmon, Rinat; Geraghty, Daniel E.; Hviid, Thomas Vauvert F.
Abstract: Introduction: The pathogenesis of preeclampsia may involve inadequate trophoblast invasion caused by excessive inhibition of uterine natural killer cells (uNK) by extravillous trophoblast cells (EVT). This may be the result of a combination of maternal killer-cell immunoglobin-like receptor (KIR) AA genotype and fetal human leukocyte antigen-C2 (HLA-C2) genotype. A few studies have reported a significantly increased frequency of the maternal KIR AA/fetal HLA-C2 combination in cases of preeclampsia compared to controls. Methods: Study subjects were 259 cases of severe preeclampsia/eclampsia and 259 matched pregnant women without preeclampsia or eclampsia. All pregnancies were singleton pregnancies, and mothers were preferentially primigravidae. Blood samples from women and their newborns were obtained from the Danish National Birth Cohort (DNBC) and the Danish Neonatal Screening Biobank. Significant differences in the frequencies of KIR AA and HLA-C2 between cases and controls were investigated. Results: No significant difference was observed between cases and controls in the frequency of maternal KIR AA (OR = 0.86, 95%CI = 0.60–1.23, P =  0.41), neither when the fetus carried an HLA-C2 allele (OR = 0.85, 95%CI = 0.52–1.38, P =  0.51), nor when the fetus carried an HLA-C2 allele more than its mother (OR = 0.75, 95%CI = 0.34–1.64, P =  0.47). Conclusion: The Results show no influence of HLA-C/KIR genetic variation on the risk of severe preeclampsia, contrary to what some previous studies have observed. An explanation could be that severe preeclampsia represents a separate pathological entity compared to mild preeclampsia. Highlights: HLA-C genotypes (C1C1/C1C2/C2C2) are similar in severe preeclampsia and controls. KIR genotype frequencies (AA/AB/BB) are similar in severe preeclampsia and controls. KIR AA genotype is not increased in preeclamptic mothers with fetal HLA-C2 allele. HLA-C/KIR genetic variation does not influence the risk of severe preeclampsia.